Flood Disaster Resilience in Kroya District, Cilacap Regency at the Household Level - Nugroho, Agung; Nurhadi, N; Noviani, Rita (Universitas Muhammadiyah Surakarta, 2024)
This scientific study was written to analyze the level of resilience to flood disasters in Kroya District, Cilacap Regency at the household level. This writing was designed as a qualitative and quantitative research model with case studies to determine how adaptation efforts function to reduce the level of vulnerability. So it is expected that there will be a difference between current vulnerabilities and future vulnerabilities. This difference is called resilience, which in this study will be explained at the household level. This research used a survey approach to obtain data from the people of Bunju Village and Mujur Village in Kroya District, Cilacap Regency. The results of the research show that the average resilience level results of Buntu Village and Mujur Village are categorized as high resilience, Buntu Village with a resilience level value of 0.695 (research value conversion) and Mujur Village with a resilience level value of 0.721 (research value conversion). So it can be concluded that the people of these two areas are ready to face the danger of a flood disaster if it occurs.